INCREASING CREATIVE COMPETENCE OF STUDENTS AND STRENGTHENING EDUCATIONAL EFFICIENCY BASED ON INDIVIDUAL APPROACH - Zulfiya Aytbаyevna Jumaniyazova (Web of Journals Publishing, 2024)
On the fundamental principles of forming a competency-based approach in the paradigm of modern education, which allows for the assignment of an important didactic goal to students' independent work.
Keywords: pragma, competence, didactic, creative, process, method, direction, interactive.